Avaliação do risco cardiovascular em pacientes com hepatites virais - ZANDONADI, Alessandra Maria Assunção (2023)
Introduction: The vulnerability to cardiovascular disease (CVD) development in patients with viral hepatitis is recurrent, due to metabolic changes, the individual is susceptible to increased visceral fat, indicating the risk for CVD. Thus, some anthropometric parameters can be used to identify cardiovascular risk. Objective: To analyze the anthropometric parameters of risk identification for cardiovascular diseases in patients diagnosed with hepatitis C. Methodology: a crosssectional, analyticaldescriptive study in which were evaluated patients attended at the Clinic of the Fundação Santa Casa de Misericórdia do Pará (FSCMPA), aged 2574 years, both sexes, diagnosed with hepatitis C, regardless of the stage of the disease. Through the use of the Informed Consent Term (TCLE) the data collection was carried out from September to November 2017. Initially, a form was applied comprising sociodemographic issues, clinical history, biochemical exams and life habits. After that, anthropometric evaluation was carried out, measuring the weight, height, waist and hip circumference of the patients, and for the anthropometric parameters of cardiovascular risk were calculated: body mass index (BMI), waist ratio and height (CC / E), waist and hip ratio (CC / QC), visceral adiposity index (VAI). Data analysis was carried out in the PROC FREQ software of SAS version 9.3 (SAS Inst, Inc. Cary, NC) and stored in spreadsheets of the Excel 2006 program. Results: 43 patients participated, of which 51.16% were male. The mean age was 58.02 years (± 13.23). Regarding the patients' life habits, 65.12% did not practice physical activity. Regarding the biochemical parameters, only LDL cholesterol presented inadequacy (55.81%). Concerning the anthropometric parameters, the adults were diagnosed as overweight (52.94%) and the elderly in eutrophy (52.00%). When the parameters for CVD were evaluated, risk was observed in CC / QC (55.81%), CC / E (81.48%) and VAI (72.09%). When analyzing the VAI in relation to the other parameters, it was observed that people with a waist / high height ratio were 13 times more likely to present high VAI. Conclusion: The cardiovascular risk was identified in the patients through all the anthropometric parameters evaluated, proving the importance of nutritional monitoring in hepatitis C. In addition, the relationship between VAI and CC / E was observed. It is suggested the efficiency of CC / E in the nutritional care to identify the cardiovascular risk, in the impossibility of evaluation through the VAI.